Praktek Meditasi Sebagai Upaya Meningkatkan Konsentrasi Belajar Pendidikan Agama Hindu Pada Siswa Di SMP Wisata Sanur - Purnajati, I Wayan; Suyanta, I Wayan (Cetta: Jurnal Ilmu Pendidikan, 2022)
Religious education is very important for students to get at school to help build good character. The importance of religious education means that students must be able to understand their learning well. Good understanding will be achieved when students have good study concentration. Good learning concentration can be achieved by focusing the students' minds. Meditation is a form of effort to focus the human mind so that it is not influenced by everything around it. This article discusses the meditation practice applied to class 8J students at SMP Wisata Sanur before Hindu Religious Education lessons were implemented. The research method used in this scientific article is a qualitative method with a descriptive approach, meaning that all the issues presented in this research are explained in detail and holistically. Then the data collection methods used are: (1) observation, (2) interviews, (3) documentation, and (4) literature study. The results of this research explain that the implementation of meditation in Hindu religious education learning in class 8J of SMP Wisata Sanur is carried out in several stages, namely preparing the students themselves, regulating their breath, focusing on the object of meditation and ending the meditation. In practice, there are several obstacles such as uncomfortable class conditions, difficulty imagining the meditation object in the form of an omkara image, influence from surrounding friends and drowsiness. Of these several obstacles, efforts have been made to overcome the obstacles that occur, namely preparing comfortable classroom conditions, practicing omkara drawing and practicing meditation at each student's home, good student seating arrangements and providing unique and interesting affirmations before practicing meditation.